Projection Methods and a New System of Extended General Regularized Nonconvex Set-Valued Variational Inequalities - Javad Balooee; Yeol Je Cho; Mee Kwang Kang (Journal of Applied Mathematics)
A new system of extended general nonlinear regularized nonconvex set-valued variational inequalities is introduced, and the equivalence between the extended general nonlinear regularized nonconvex set-valued variational inequalities and the fixed point problems is verified. Then, by this equivalent formulation, a new perturbed projection iterative algorithm with mixed errors for finding a solution of the aforementioned system is suggested and analyzed. Also the convergence of the suggested iterative algorithm under some suitable conditions is proved.